STUDY OF THE IMPACT OF MOX FUEL VARIATIONS ON THE OPERATIONAL CYCLE OF NUSCALE REACTOR - Lola Febryandini Hasibuan; Dian Fitriyani; Helen Raflis (Universitas Andalas, 2026)
This study analyzes the effect of Mixed Oxide (MOX) fuel variations on the operational cycle of the NuScale reactor. The MOX fuel variations used include monoThPu, monoUPu, multiUPu, multiThUPu, and multiTh, with a focus on changes in the isotopic composition of plutonium, uranium, and thorium. The modeling was performed using the OpenMC code based on the Monte Carlo method with the ENDF/B-VIII.0 nuclear data library. A core design modification was made in Batch A-01 by replacing the standard uranium fuel with MOX variations without gadolinia. The simulation results show that all MOX configurations are supercritical at beginning of the cycle () and gradually decrease to the refueling limit (). The monoThPu, monoUPu, multiUPu, and multiThUPu fuels can maintain criticality for up to 24 months of operation, whereas multiTh achieves only 16 months. Fuels with higher fissile isotope fractions, such as Pu-239 and Pu-241, produce sharper neutron flux distributions at the core center, while the dominance of Th-232 in multiTh results in a more uniform flux profile. The Power Peaking Factor (PPF) values remain within the thermal design safety limit (PPF < 1.3).